Methanogenic food web in the gut contents of methane-emitting earthworm Eudrilus eugeniae from Brazil - Schulz, Kristin (ISME J, 2015)
The anoxic saccharide-rich conditions of the earthworm gut provide an ideal transient habitat for ingested microbes capable of anaerobiosis. It was recently discovered that the earthworm Eudrilus eugeniae from Brazil can emit methane (CH(4)) and that ingested methanogens might be associated with this emission. The objective of this study was to resolve trophic interactions of bacteria and methanogens in the methanogenic food web in the gut contents of E. eugeniae. RNA-based stable isotope probing of bacterial 16S rRNA as well as mcrA and mrtA (the alpha subunit of methyl-CoM reductase and its isoenzyme, respectively) of methanogens was performed with [(13)C]-glucose as a model saccharide in the gut contents. Concomitant fermentations were augmented by the rapid consumption of glucose, yielding numerous products, including molecular hydrogen (H(2)), carbon dioxide (CO(2)), formate, acetate, ethanol, lactate, succinate and propionate. Aeromonadaceae-affiliated facultative aerobes, and obligate anaerobes affiliated to Lachnospiraceae, Veillonellaceae and Ruminococcaceae were associated with the diverse fermentations. Methanogenesis was ongoing during incubations, and (13)C-labeling of CH(4) verified that supplemental [(13)C]-glucose derived carbon was dissimilated to CH(4). Hydrogenotrophic methanogens affiliated with Methanobacteriaceae and Methanoregulaceae were linked to methanogenesis, and acetogens related to Peptostreptoccocaceae were likewise found to be participants in the methanogenic food web. H(2) rather than acetate stimulated methanogenesis in the methanogenic gut content enrichments, and acetogens appeared to dissimilate supplemental H(2) to acetate in methanogenic enrichments. These findings provide insight on the processes and associated taxa potentially linked to methanogenesis and the turnover of organic carbon in the alimentary canal of methane-emitting E. eugeniae.